An Evaluation of the Use of Flashcard for Teaching Vocabulary at Kindergartens in Sintang - Henry Elisa; Tuti Tuti (JETL (Journal of Education, Teaching and Learning), 2020)
Vocabulary plays an important role in determining the students’ ability for speaking because it is basic before children can produce words. Therefore, the teacher needs media as a tool to introduce those words to their students in the classroom. Flashcards is one of the media usually used by teachers at kindergartens in the Sintang Regency for teaching vocabulary for young learners. This research aims to evaluate the effects of using flashcard media for teaching vocabulary and identify the teachers’ responses towards the use of flashcard media for teaching vocabulary at kindergartens in Sintang Regency, West Kalimantan. This descriptive research qualitative research as an evaluation study is designed to explore the effects of the media on the students and teachers’ perspective. The data in this research were gathered through questionnaires with fifty-one participants and a semi-structured interview with five participants in Sintang Regency. The data analysis techniques used scale Likert in order researchers know how the use of flashcards by the teachers. The study’s results revealed that teachers believe that using flashcards is essential for teaching vocabulary to young learners. Thus, the teachers have various flashcards that can be applied for teaching vocabulary to young learners, for using colourful flashcards with different sizes. It is expected that this research gives references and knowledge for the kindergarten teachers who teach young learners so they could use the same media but with different types of flashcards types.